A study of oral pre-malignant lesions and related risk factors - Varshney, Saurabh; Sandhir, Shivanjali; Mishra, Sarita (Indian Journal of Community Health, 2015)
Introduction: The occurrence of oral pre-malignant lesions is related to social behavior and addictive habits of the individual. The type of lesions differs from one geographic area to other. There is paucity of data on oral pre- malignant lesion occurring in the state of Uttarakhand. Though not all oral carcinomas are preceded by premalignant lesions as clinically visible morphological alterations occur secondary to the cellular or molecular changes. Their management remains controversially polarized between surgical excision to prevent malignant change and conservative medical or surveillance techniques. Material and Methods: It was an observational cross sectional study for one year. 77 cases of oral pre-malignant lesions attending E.N.T. OPD were studied. The lesions included were leukoplakia, oral submucous fibrosis and erythroplakia. Result: The males were affected more than females. The male: female ratio was 4.13:1. The most affected age group was 31-40 years (36.36%). The leukoplakia cases were 45 (58.45%), oral submucous fibrosis 26 cases (33.76%) and erythroplakia- 6 cases (7.79%). The habit of tobacco use was found to be a risk factor for development of these conditions. Conclusion: The leukoplakia is more common than oral submucous fibrosis. There is correlation between tobacco use and premalignant conditions. The occurrence of oral submucous fibrosis is related to chewable tobacco or other chewable products. The leukoplakia is associated with smoking and its association with alcohol misuse needs further studies